2002
DOI: 10.1103/physrevlett.89.113002
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Pathways in Strong Field Atomic Ionization Dynamics

Abstract: With the help of a suitably chosen momentum-space analysis, we study some of the basic mechanisms governing the physics of the processes occurring when atoms are submitted to intense infrared laser pulses, with peak intensities 10(14) W cm(-2) Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…51,52 This is in line with the fact that in conductivity models, two-stage processes are often adopted. However for the hydrogen atom, a pure tunneling mechanism does not fit with numerical solutions of the time-dependent Schrödinger equation, and it is indicated that an indirect tunneling mechanism is important.…”
Section: Two-stage Processmentioning
confidence: 62%
“…51,52 This is in line with the fact that in conductivity models, two-stage processes are often adopted. However for the hydrogen atom, a pure tunneling mechanism does not fit with numerical solutions of the time-dependent Schrödinger equation, and it is indicated that an indirect tunneling mechanism is important.…”
Section: Two-stage Processmentioning
confidence: 62%
“…Research in the last two decades has confirmed that Coulomb focusing (and the Coulomb field in general) is a key player in the recollision process [8][9][10][11][12]. But it seems that the opposite question -namely, when the Coulomb focusing does not matter-has not received the same attention.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been identified as responsible for the low-energy structure [51,52] and the ionization suppression in the extremely-low-energy part of the ATI spectra [53] measured in experiments. Theoretical results have indeed shown that such features are due to the presence of the Coulomb potential [49,54]. Therefore, it is important to stress how our results would be modified should the residual binding potential be included in our computations.…”
Section: Discussionmentioning
confidence: 85%
“…On a quantitative level, it underestimates the ionization rates for direct ATI, as compared to the TDSE. For studies of how the SFA behaves as compared to the TDSE for several driving-field wavelengths, see [49,50].…”
Section: Discussionmentioning
confidence: 99%